2023
DOI: 10.1096/fj.202200216rrrr
|View full text |Cite
|
Sign up to set email alerts
|

Presequence protease reverses mitochondria‐specific amyloid‐β‐induced mitophagy to protect mitochondria

Abstract: Amyloid‐β (Aβ) peptide is accumulated in the mitochondria and has been shown to play a central role in the development of Alzheimer's disease (AD). It has been shown that exposure of neurons to aggregated Aβ can result in damaged mitochondria and dysregulated mitophagy, indicating that changes in the Aβ content of mitochondria may affect the levels of mitophagy and interfere with the progression of AD. However, the direct influence of mitochondrial Aβ on mitophagy has not been elucidated. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Dou and Tan transfected SHSY-5Y human neuroblastoma cells with plasmids harboring mitochondrial outer membrane protein translocase (TOMM)22 and TOMM40 to directly augment mitochondrial Aβ content. They found that increased Aβ content in the mitochondria enhanced mitophagy, and this could be reversed by transfection with a plasmid harboring presequence protease, responsible for Aβ degradation [76]. In a separate study, presequence protease activity was found by Alikhani and colleagues to be significantly lower in mitochondria isolated from brain tissue specimens obtained post-mortem from the temporal region of AD-affected subjects compared to age-matched controls [77].…”
Section: Aβ and Tau In Mitophagy And Mitochondrial Movementmentioning
confidence: 97%
“…Dou and Tan transfected SHSY-5Y human neuroblastoma cells with plasmids harboring mitochondrial outer membrane protein translocase (TOMM)22 and TOMM40 to directly augment mitochondrial Aβ content. They found that increased Aβ content in the mitochondria enhanced mitophagy, and this could be reversed by transfection with a plasmid harboring presequence protease, responsible for Aβ degradation [76]. In a separate study, presequence protease activity was found by Alikhani and colleagues to be significantly lower in mitochondria isolated from brain tissue specimens obtained post-mortem from the temporal region of AD-affected subjects compared to age-matched controls [77].…”
Section: Aβ and Tau In Mitophagy And Mitochondrial Movementmentioning
confidence: 97%
“…Amyloid plaques formed by β-amyloid (Aβ) and neurofibrillary tangles formed by abnormally modified tau proteins are the hallmarks of AD ( Skouras et al, 2020 ; Ossenkoppele et al, 2022 ; Tautou et al, 2023 ). Aβ is a peptide produced by hydrolysis of amyloid precursor protein (APP), and excess Aβ accumulation in mitochondria activates astrocytes and microglia, damages neurons ( Huang et al, 2023 ), and induces mitochondrial autophagy, promoting reactive oxygen species (ROS) production and accelerating neural oxidation ( Dou and Tan, 2023 ). At the same time, over-phosphorylation of tau protein eliminates its ability to form and maintain stable microtubules, reduces the dissociation of microtubule protein molecules, and induces microtubule bundling ( Kandimalla et al, 2018 ; Solas et al, 2023 ; Zhang et al, 2023 ).…”
Section: Co-morbidity Hypothesismentioning
confidence: 99%
“…However, whilst the interaction of Aβ with HSD10 causes a prompt increase in ROS levels, namely O 2 · − and H 2 O 2 , and a loss of mitochondria function [ 50 ], PreP activity was found to be decreased in AD brains and AD transgenic mouse brains, which also presented higher levels of oxidative products in their mitochondria [ 49 ]. It has been therefore proposed that modulating PreP activity could be a feasible strategy to control the mitochondrial Aβ content and mitochondrial oxidative stress [ 51 , 52 ]. Moreover, a recent in vitro study performed in iPSC-derived neurons and SY5Y cells transfected with an AβPP construct identified an undescribed correlation between the mitochondrial membrane potential, AβPP mitochondrial localization, and Aβ secretion [ 53 ].…”
Section: Mitochondria (Dys)function In Alzheimer’s Disease: a Brief O...mentioning
confidence: 99%